PERBANDINGAN PENDEKATAN SEPARABLE PROGRAMMING DENGAN THE KUHN-TUCKER CONDITIONS DALAM PEMECAHAN MASALAH NONLINEAR - Marpaung, Budi (Teknik dan Ilmu Komputer, 2012)
Separable Programming is the approach used to solve nonlinier problems with the Simplex Method. This method is proven to solve nonlinier problem, which until now has no way like the standard linear programming problems. This paper tries to compare the process and results of  Separable Programming approach to the Kuhn-Tucker Condition. Proved that both give similar result, but in a different way. Separable Programming Approach should be used to solve nonlinear problems who have difficulty when solved by the Kuhn-Tucker  Conditions Approach.  Keywords:  separable programming, the Kuhn-Tucker Conditions, nonlinier programming, grid point, convex, concave, criteria, formulation, optimal